2012
DOI: 10.1172/jci63915
|View full text |Cite
|
Sign up to set email alerts
|

Activation of KATP channels suppresses glucose production in humans

Abstract: The anti-Fpn and anti-Jak2 rows in Figure 2A Figure 3B of that manuscript.The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
2
12
1
Order By: Relevance
“…Although C-peptide levels were slightly higher with the onset of hyperglycaemia during HY and HY-NEFA, compared with EU, they were comparable and would therefore not be expected to contribute to differences between these groups ( Table 1). The portal insulin levels attained with this protocol are likely to reproduce physiological fasting conditions, given an anticipated portal/systemic insulin ratio of ∼2.4:1, as previously described [20,21]. With fasting systemic insulin levels of ∼80 pmol/l in our participants, corresponding fasting portal levels would approximate 192 pmol/l, which is consistent with the systemic levels observed during the final hour of these clamp studies.…”
Section: General Clamp Study Conditionssupporting
confidence: 80%
“…Although C-peptide levels were slightly higher with the onset of hyperglycaemia during HY and HY-NEFA, compared with EU, they were comparable and would therefore not be expected to contribute to differences between these groups ( Table 1). The portal insulin levels attained with this protocol are likely to reproduce physiological fasting conditions, given an anticipated portal/systemic insulin ratio of ∼2.4:1, as previously described [20,21]. With fasting systemic insulin levels of ∼80 pmol/l in our participants, corresponding fasting portal levels would approximate 192 pmol/l, which is consistent with the systemic levels observed during the final hour of these clamp studies.…”
Section: General Clamp Study Conditionssupporting
confidence: 80%
“…Consistent with findings in rodents that ICV infusion of the K ATP channel activator diazoxide decreased EGP (12), our group recently reported the first studies in humans suggesting central regulation of EGP (78). We performed euglycemic "pancreatic clamp" studies, using somatostatin to inhibit endogenous insulin secretion along with replacement of basal insulin and glucoregulatory hormones following administration of diazoxide in healthy subjects.…”
Section: Evidence From Human Studies Supporting Cns Regulation Of Metsupporting
confidence: 52%
“…Of note, complementary studies in rats (78) showed that diazoxide crosses the blood-brain barrier and confirmed the suppression of EGP during euglycemic pancreatic clamp studies following oral diazoxide, along with decreases in glucose 6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK) expression and increased hepatic STAT3 phosphorylation. When the K ATP channel blocker glibenclamide was administered ICV in rats, the effects of oral diazoxide on EGP, gluconeogenic enzyme expression, and hepatic STAT3 phosphorylation were completely abolished (78). Together, these studies strongly suggest that hypothalamic K ATP channels regulate EGP, at least in part, in humans as well as in rodents.…”
Section: Evidence From Human Studies Supporting Cns Regulation Of Metmentioning
confidence: 81%
“…The current study demonstrates that the activation of MBH K ATPchannels, per se, attenuates hepatic VLDL-TG secretion and plasma TG levels in a model of HFD-induced hypertriglyceridemia. Given that orally administered diazoxide, which increased CSF levels of diazoxide and activated brain K ATPchannels in parallel complementary studies in rodents, lowers glucose production in humans 51 , it would be important to assess whether diazoxide lowers VLDL-TG secretion in humans and alternative experimental rodent models with obesity, diabetes and lipid disorders such as the fructose-fed hamster and the apoEdeficient and/or LDLR-deficient mice. Diazoxide inhibits b-cell insulin secretion 52 , and since circulating insulin negatively regulates hepatic VLDL-TG release 14 , systemic diazoxide may not reduce VLDL-TG secretion.…”
Section: Discussionmentioning
confidence: 99%